The Road to Academic Excellence : The Making of World-Class Research Universities - Altbach, Philip G. (World Bank, 2012)
For middle-income and developing countries as well as some industrial nations a major challenge for building and sustaining successful research universities is determining the mechanisms that allow those universities to participate effectively in the global knowledge network on an equal basis with the top academic institutions in the world. These research universities provide advanced education for the academic profession, policy makers, and public and private sector professionals involved in the complex, globalized economies of the 21st century. In addition to their contribution to economic development, these universities play a key societal role by serving as cultural institutions, centers for social commentary and criticism, and intellectual hubs. The positive contribution of tertiary education is increasingly recognized as not limited to middle-income and advanced countries, because it applies equally to low-income economies. Tertiary education can help these countries to become more globally competitive by developing a skilled, productive, and flexible labor force and by creating, applying, and spreading new ideas and technologies. A recent study on how to accelerate economic growth in Sub-Saharan Africa spells out the crucial contribution of tertiary education in supporting this endeavor (World Bank 2008). It observes that the key for success in a globalized world increasingly lies in how effectively a country can assimilate available knowledge and build comparative advantages in areas with higher growth prospects and how it can use technology to address the most pressing environmental challenges. The main chapters of this book are nine case studies that illustrate what it takes to establish and sustain research universities and help validate the analytical model outlined above, including the paths to building research excellence.